Faktor-Faktor yang Mempengaruhi Pembelian Apartemen Mewah, The Stature Jakarta - Inesencia, Anastasia (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The need for a home is one of the basic human needs. Currently home ownership is not only intended for the fulfillment of basic needs only, but has become an interesting investment alternative in Jakarta, one of the centers of economic growth with the rate of population increase is quite high in Indonesia. Population growth that occurs either naturally or through the process of urbanization led to a growth in demand for residential houses. It is boosting the development of the city of Jakarta Property in good simple house to luxury Property. The research result is consumer property in the city of Jakarta, in buying luxury property prefers factors.